2001
DOI: 10.1002/jso.10043
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in well‐differentiated thyroid cancer patients treated with suppressive thyroxine: A systematic overview of the literature

Abstract: Although studies were limited by small numbers and varying degrees of control for confounding variables, results suggested no significant change in bone mineral density for premenopausal women or men. Findings for postmenopausal women remain unclear with two of the best controlled studies reporting opposing results. Further studies for this population are recommended to help guide clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 29 publications
3
38
0
6
Order By: Relevance
“…Heemstra et al (2006) analysed four prospective and 12 cross-sectional studies of pre-menopausal women receiving suppressive doses of T 4 , and concluded that treatment with suppressive doses of T 4 did not affect BMD, although a full meta-analysis could not be performed due to heterogeneity. This conclusion was consistent with two preceding systematic literature reviews (Faber & Galloe 1994, Uzzan et al 1996, Quan et al 2002, Murphy & Williams 2004, Heemstra et al 2006 and two meta-analyses (Faber & Galloe 1994, Uzzan et al 1996. Currently, there are no prospective data on fracture risk in pre-menopausal women receiving suppressive doses of T 4 .…”
Section: Suppressive Doses Of T 4 In Differentiated Thyroid Cancersupporting
confidence: 87%
“…Heemstra et al (2006) analysed four prospective and 12 cross-sectional studies of pre-menopausal women receiving suppressive doses of T 4 , and concluded that treatment with suppressive doses of T 4 did not affect BMD, although a full meta-analysis could not be performed due to heterogeneity. This conclusion was consistent with two preceding systematic literature reviews (Faber & Galloe 1994, Uzzan et al 1996, Quan et al 2002, Murphy & Williams 2004, Heemstra et al 2006 and two meta-analyses (Faber & Galloe 1994, Uzzan et al 1996. Currently, there are no prospective data on fracture risk in pre-menopausal women receiving suppressive doses of T 4 .…”
Section: Suppressive Doses Of T 4 In Differentiated Thyroid Cancersupporting
confidence: 87%
“…Consequently, thyrotoxicosis is an important cause of secondary osteoporotic fracture (Mosekilde et al 1990, Cummings et al 1995, Franklyn et al 1998, Vestergaard et al 2000, Vestergaard & Mosekilde 2002, Murphy & Williams 2004) and even subclinical hyperthyroidism has been associated with decreased bone mineral density and increased fracture risk in postmenopausal women (Bauer et al 2001, Quan et al 2002, Murphy & Williams 2004, Heemstra et al 2006, Kim et al 2006, Morris 2007.…”
Section: Thyroid Hormone Receptor Mutant Micementioning
confidence: 99%
“…L-T4 therapy may also be accompanied by iatrogenic latent or even overt hyperthyroidism. Overt hyperthyroidism is associated with an increased risk of osteoporosis, while whether subclinical hyperthyroidism affects the skeleton is under debate [7,8]. Effects of the latter on bone mineral density (BMD) have been addressed in a number of studies with somewhat controversial results [9][10][11][12][13][14][15].…”
mentioning
confidence: 99%